Knowledge and Agency. The Case of Claes Rålamb and the Swedish Embassy to Istanbul, 1657–58 - Forss, Charlotta (Legatio: The Journal for Renaissance and Early Modern Diplomatic Studies, 2022)
This article explores the interplay between knowledge and agency in early modern diplomacy. Focusing on the power dynamics of early modern empire through a case study of a Swedish embassy to the Ottoman Empire in 1657–58, the article shows how agency and knowledge interlinked throughout the diplomatic mission. At the centre of the study is Claes Rålamb, a Swedish nobleman who was sent to Istanbul to secure an alliance between Sweden and the Ottoman vassal state Transylvania. Rålamb’s journey to, and stay in, Istanbul was framed by global political developments, yet, it was also directly influenced by local customs and personal connections. In particular, Rålamb’s ability to act as an agent of the Swedish Empire was shaped by the difficulties of attaining reliable information. Moreover, the framework within which he was able to act changed between different stages of the journey. This makes the intersection between knowledge and agency a fruitful focal point for examining early modern empire, going beyond traditional national frameworks and categories of actors. Rålamb was sent out as an envoy of the Swedish empire, yet the meaning of that position changed constantly.